Papular xanthomas and erosive arthritis in a 3 year old girl, is this a new MRH variant? - Groh Brandt; Zaenglein Andrea; Ferguson Polly J; Matiz Catalina; Bingham Catherine (BMC, 2009)
Abstract Xanthomatous skin lesions and arthritis in children are not a common association. We present the case of a 3 year old girl who presented with xanthomatous lesions in the periungual region of both hands, around the nares and on her forehead, associated with significant arthritis that was clinically compatible with multicentric reticulohistiocytosis. However, pathology of the xanthomatous lesions was more suggestive of papular xanthoma, a disease that is not associated with arthritis. Based on her presentation and the negative lipid workup, she was treated for presumed multicentric reticulohistiocytosis. Multiple treatment strategies were utilized, with improvement on a combination of infliximab, methotrexate, and prednisone. We review the different diagnoses that should be considered in children with xanthomas and arthritis as well as the different pharmacologic therapies used in children with multicentric reticulohistiocytosis.